Prebiotic Properties of Carbohydrates in the Formation of Children's Health - N.G. Mikryukova (Zaslavsky O.Yu., 2013)
Сontent of dietary fibers, pectin and fibers in modern products is studied. The necessity for dysbiosis prevention is established on the basis of prebiotic properties of carbohydrates providing a synthesis of metabolites of two types (macroorganism and endoecosystem). Classification of dietary fibers is grounded taking into account modern position.